Numerical Simulation of the Stability of Rock Mass around Large Underground Cavern - Dang Van Kien; Do Ngoc Anh; Do Ngoc Thai (Salehan Institute of Higher Education, 2022)
Geotechnical problems are complicated to the extent and cannot be expected in other areas since non-uniformities of existing discontinuous, pores in materials and various properties of the components. At present, it is extremely difficult to develop a program for tunnel analysis that considers all complicated factors. However, tunnel analysis has made remarkable growth for the past several years due to the development of numerical analysis method and computer development, given the situation that it was difficult to solve formula of elasticity, viscoelasticity, and plasticity for the dynamic feature of the ground when the constituent laws, yielding conditions of ground materials, geometrical shape and boundary conditions of the structure were simulated in the past. The stability of rock mass around an underground large cavern is the key to the construction of large-scale underground projects. In this paper, the stability analysis was carried out based on those parameters by using 2D FEM RS2 program. The calculated stress and displacements of surrounding rock and rock support by FEM analysis were compared with those allowable values. The pattern of deformation, stress state, and the distribution of plastic areas are analyzed. Finally, the whole stability of surrounding rock mass of underground caverns was evaluated by Rocscience - RS2 software. The calculated axial forces were far below design capacity of rock bolts. The strong rock mass strength and high horizontal to vertical stress ratio enhanced safe working conditions throughout the excavation period. Thus wide span caverns and the system of caverns could be stability excavated sedimentary rock during the underground cavern and the system of caverns excavation by blasting method. The new method provides a reliable way to analyze the stability of the caverns and the system of caverns and also will help to design or optimize the subsequent support. Doi: 10.28991/CEJ-2022-08-01-06 Full Text: PDF